2008
DOI: 10.4028/www.scientific.net/ddf.273-276.536
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Homogenization Treatment in Al- Li- Cu- Zr Alloys

Abstract: Aluminum-Lithium alloys were developed as major replacements for existing aluminum alloys to reduce the weight of aircraft and aerospace structures. Mechanical properties of Al-Li alloys greatly depend on solidification conditions. Other than reducing the microsegregation, homogenization treatment has other effects on the microstructure of Al-Li ingots. In this research, effects of homogenization treatment at constant temperature (500°C) on the precipitation in the microstructure of Al-1Li-3Cu-0.1Zr (wt %) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
Order By: Relevance
“…The last case (after 48h of heat treatment) exhibited the lowest microhardness value. The SEM and optical images can explain it as they show no precipitates at the grain boundaries, indicating precipitates dissolution and coarsened grains This phenomenon aligns with the findings of Rezaei et al [ 12 ] who investigated two Al–Li alloys with Al–3Cu-1(2)Li-0.1Zr chemical composition and found a fluctuation in hardness depending on the homogenization time at a constant temperature of 500 °C.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The last case (after 48h of heat treatment) exhibited the lowest microhardness value. The SEM and optical images can explain it as they show no precipitates at the grain boundaries, indicating precipitates dissolution and coarsened grains This phenomenon aligns with the findings of Rezaei et al [ 12 ] who investigated two Al–Li alloys with Al–3Cu-1(2)Li-0.1Zr chemical composition and found a fluctuation in hardness depending on the homogenization time at a constant temperature of 500 °C.…”
Section: Resultssupporting
confidence: 88%
“…For instance, Wei et al [ 11 ] studied a systematic homogenization heat treatment on an Al–Li–Cu–Mg–Zr alloy and found that the best combination was 530 °C for 24h, followed by air cooling. Rezaei et al study [ 12 ] investigated the homogenization of an Al–1Li–3Cu-0.1Zr and Al–2Li–3Cu-0.1 Zr concluding that the heat treatment should be conducted at 500 °C for 24 h. Zhang et al [ 13 ] examined the as-cast and homogenized AA2099 alloy, revealing the presence of a severe dendritic structure. They optimized the heat treatment process in a two-step approach (515 °C for 18h followed by 525 °C for 16h).…”
Section: Introductionmentioning
confidence: 99%